Peranan Faktor Lingkungan terhadap Penyakit Antraknos pada Bawang Merah - Bambang Hadisutrisno (Jurnal Perlindungan Tanaman Indonesia, 1999)
Anthrachnose caused by Colletotrichum gloeosporioides (Penz.) Sacc. is one of the most important disease on shallot. Study on its ecological aspects is still limited. The results of the study revealed that anthracnose could be found at various ages of the plant. The climatic factor that had strong effect on the disease intensity was period of rain. The highest disease intensity (more than 54.89 percent) was obtained at plantation when it rained between 08.00–10.00 p.m., while the lowest occurred when it rained between 04.00–06.00 a.m.